STUDENTS’ PERCEPTIONS ON THE USE OF YOUTUBE VIDEOS FOR SPEAKING ACTIVITIES - Ivada Hasni (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
This research presents the perceptions of eighth-grade students of SMP Islam Ma’arif 03 Malang on the use of YouTube for speaking activities.The research used a descriptive qualitative approach with a descriptive study as the research design. The subjects were 26 eighth-grade students of SMP Islam Ma’arif 03 Malang. To investigate students’ perceptions, the researcher used an online questionnaire and interview as the methods of collecting data. Then, the instruments used by the researcher were an online questionnaire and interview. The findings of this study showed that the perceptions of the students on the use of YouTube for speaking activities were positive. Most of them agreed that the use of YouTube videos can help them to comprehend faster and better in learning English speaking skills, use proper vocabulary, use correct grammatical forms, and reduce their anxiety so that they can speak English in class with their friends and teacher. In the future, researchers can use more subjects or different educational levels and can also use other questionnaires to get better results.STUDENTS’ PERCEPTIONS ON THE USE OF YOUTUBE VIDEOS FOR SPEAKING ACTIVITIES